Molecular docking analysis to validate the efficacy of Polyherbal Siddha Formulation Seethabedhi Chooranam for Anti-diarrhoeal activity - Rakulini, S.; Sounthararajan, K.; Sivashanmugarajah, S. (University of Jaffna, 2024)
Siddha Medicine is considered one of the oldest traditional systems of medicine in the world. Herbal remedies play a significant role in Siddha Medicine. The system utilizes a wide range of herbs, metals, minerals, marine, and animal origin to prepare medicines. Polyherbal formulations are common, and the combination of ingredients is believed to enhance therapeutic effects. Molecular docking analysis is a computational approach to predict the binding affinity and interactions between small molecules and target proteins. This technique plays a vital role in the process of drug discovery and design, helping researchers understand the interactions between potential drug compounds and their target proteins. The M3 muscarinic acetylcholine receptor was used as the target receptor in docking calculations for recovered phytocomponents. Five bioactive lead compounds were retrieved from the herbs present in the formulation Seethabedhi Chooranam. According to documented data on the herbs, the main constituents, namely β-caryophyllene, Quercetin and Eugenol have a 100% binding efficacy when they interact with the core target amino acids (Ser151, Tyr529, Tyr506, and Trp503) that are present on the target, on the other hand Cinnamic acid and Kaempferol have a 90% binding efficacy with target amino acid when compared with the standard Loperamide which has a 100 % binding efficacy on the M3 muscarinic acetylcholine receptor (PDB- 4U14). The bio-active compounds were found to exhibit significant binding against the target protein, as indicated by computational analysis results. This suggests that the compounds may have promising anti-diarrheal properties by impeding the activity of the M3 muscarinic acetylcholine receptor, which is present in the intestinal region that mediates the diarrhea.
Keywords: Siddha Medicine; In-silico; Docking study; Seethabedhi chooranum; M3 muscarinic acetylcholine receptor